The Rhetoric of the Imagery of Muhammad Marzuki's (Zuk) Painting with the Theme of Human Arrogance Uploaded on Instagram Account - Aizza Nur Layli Eni Sukaesih; Albertus Rusputranto Ponco Anggoro (Texture : Art And Culture Journal, 2025)
This study discusses the rhetoric of the image of Muhammad Marzuki's (Zuk) painting with the theme of human arrogance uploaded on his Instagram account. Zuk's painting that comes with a caption provides evidence that artwork can trigger self-reflective appreciation, because of the rhetoric (strong visual language) in the visuals and captions. The purpose of this study is to explain the background of the creation of Zuk's paintings, explain the visuality of Zuk's paintings with the theme of human arrogance, and explain the rhetoric of the image of Zuk's paintings with the theme of human arrogance. This Final Project examines the rhetoric of the image of Zuk's paintings with the theme of human arrogance uploaded on his Instagram account from the perspective of Roland Barthes' rhetorical theory of imagery using the semiotic analysis method. The researcher found that the rhetoric of Zuk's work was formed because Zuk's paintings have visual elements that are relevant to appreciation, simplicity of technique and form, and captions written in simple and relaxed language. The text in the caption relays the visual meaning of the photo, so that the message and meaning become stronger. The results of the study show that there is rhetoric (strong visual language) in the photographs of Zuk's paintings and the captions that accompany them.